Bayesian Analysis of the Lomax-Power Rayleigh (T-X) Distribution (European Journal of Pure and Applied Mathematics, 2025)
This study presents a Bayesian analysis of the Lomax-Power Rayleigh (T-X) distribution using both uniform and Jeffery priors. Bayes estimators are derived under four different loss functions: squared error loss, quadratic loss, weighted loss, and precautionary loss. The performance of the proposed estimators is demonstrated through simulation studies and a real-world dataset. Results indicate that the quadratic loss function yields the most reliable parameter estimates.
Keywords: Uniform and Jeffery priors, Loss functions, application, Bayes theorem, simulation.